The Effect of Profitability, Risk, and Company Age on ESG Disclosure - Melinda Yustin; Rousilita Suhendah (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to determine the effect of profitability, risk, and company age on the ESG disclosure of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The research uses quantitative methods and purposive sampling techniques with a sample of 41 companies that are included in the category of manufacturing companies. The processed data is secondary data from financial reports and sustainability reports obtained from the Indonesia Stock Exchange website and company websites. Data processing uses the IBM SPSS Statistics 28 application. The results show that company age has a positive and significant effect on ESG disclosure, while profitability has a negative and significant effect on ESG disclosure. Risk is known to have no significant effect on ESG disclosure.